A novel intelligent approach for color image privacy preservation - Soualmi, Abdallah; Laouamer, Lamri; Alti, Adel (Multimedia tools and applications, 2024)
Currently, specialists and researchers are focusing their efforts on information security, while frequently exchanged data is increasingly vulnerable to cyberattacks and threats. They use cryptography and watermarking methods to ensure copyright ownership protection, authenticity and integrity by hiding secret data within encrypted images. Most existing watermarking schemes are unable to ensure a good balance between imperceptibility, robustness, time processing, blindness and security. To address these problems, we propose a novel blind watermarking scheme for color images based on chaotic sequence, A-start algorithm and DCT. First, we apply DCT transform on the host image to produce DCT weights. The image block sequences are then slightly updated and scrambled from the obtained DCT weights using A-start algorithm and Arnold chaotic map. Finally, the embedded bits are extracted using the same embedding steps. Optimized image block sequences result in imperceptible, secure and robust watermark bits while reducing processing time. Experimental results show that the proposed approach outperforms other similar works when it comes to imperceptibility exceeding 74 dB and execution time less than 1.5 s for both watermark embedding and extraction. It has exceptional robustness to filtering, rotation and JPEG compression attacks with normalized correlations exceeding 0.8.